2005
DOI: 10.1002/ijc.20876
|View full text |Cite
|
Sign up to set email alerts
|

Absence of acute apoptotic response to genotoxic carcinogens in p53‐deficient mice is associated with increased susceptibility to azoxymethane‐induced colon tumours

Abstract: Acute apoptotic response to genotoxic carcinogens (AARGC) might be important for controlling the consequences of mutational load in the colon. It has been shown to occur in parallel with activation of DNA repair mechanisms. Inadequate AARGC might allow development of mutated clones with the potential to progress to cancer. In this study, we tested if p53 levels were important for AARGC in the colon and whether defective AARGC was associated with increased risk for colorectal oncogenesis. Apoptosis was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 40 publications
3
37
1
Order By: Relevance
“…[56][57][58] In contrast to the requirement for p53 to mount a normal acute apoptotic response to DNA damage, we found previously that apoptosis in tumors is not dependent on p53 status. 30 In our present study, sulindac treatment tended to increase apoptosis in tumors, even when one allele or both alleles of p53 were lost, although the effect was not significant. Others have shown that certain NSAID increase levels of apoptosis in tumors.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…[56][57][58] In contrast to the requirement for p53 to mount a normal acute apoptotic response to DNA damage, we found previously that apoptosis in tumors is not dependent on p53 status. 30 In our present study, sulindac treatment tended to increase apoptosis in tumors, even when one allele or both alleles of p53 were lost, although the effect was not significant. Others have shown that certain NSAID increase levels of apoptosis in tumors.…”
Section: Discussioncontrasting
confidence: 56%
“…36,38,39 Our previous study showed that in the presence of p53 haploinsufficiency, the apoptotic response to carcinogen is defective and is associated with an increased risk of progression to cancer after carcinogen administration. 30 Sulindac reduces this risk as we found that progression to colonic tumour formation was reduced in both wild-type and p53 1/2 mice by 53% and 41% respectively. In effect, p53 1/2 mice were not at increased risk for AOM-induced oncogenesis when given sulindac.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations